Redacciones modificadas debido a la pandemia en medios de comunicación impresos - Duarte Martillo, Jessenia del Pilar (2021)
During the confinement due to covid-19 in 2020, one of the largest communication media in Ecuador had to adapt the editorial department and that is how Diario Expreso of the city of Guayaquil was forced to rethink strategies in the writing department. The main objective of the research was to describe the employment impact of the modified newsrooms due to the pandemic in print media. A methodology with a qualitative approach was proposed, in which it has a descriptive scope. For the theoretical development, the articles, magazines, documents, among others, that are provided on the web were very useful. According to the analysis carried out, it was possible to conclude that the work of the writing team had to adapt to the teleworking modality and having technology as an ally, which through the tools it offers was very useful for all kinds of information that it was required to receive or inform, about the organization, as well as for the preparation of the newspaper.